Fractional differential equations with Atangana–Baleanu fractional derivative: Analysis and applications. (June 2019) - Syam, M.I.; Al-Refai, Mohammed
Abstract: We study linear and nonlinear fractional differential equations of order 0 < α < 1, involving the Atangana–Baleanu fractional derivative. We establish existence and uniqueness results to the linear and nonlinear problems using Banach fixed point theorem. We then develop a numerical technique based on the Chebyshev collocation method to solve the problem. As an important application we consider the fractional Riccati equation. Two examples are presented to test the efficiency of the proposed technique, where a notable agreement between the approximate and the exact solutions is obtained. Also, the approximate solutions approach to the exact solutions of the corresponding ordinary differential equations as the fractional derivative approaches 1.